Characterizing Turbulence at a Forest Edge: Comparing Sub-Filter Scale Turbulence Models in Simulations of Flow over a Canopy - Dorianis M. Perez; Jesse M. Canfield; Rodman R. Linn; Kevin Speer (Environmental Modeling & Assessment, 2026)

Response of soil nutrient pools and microbiomes to recurrent wildfire disturbance and varying burn severities in a mixed conifer forest - Alejandro Gutierrez; Marie E. Kroeger; Adam Killebrew; Eric R. Moore; Rodman Linn; Adam L. Atchley; L. Turin Dickman (Applied Soil Ecology, 2026)

A cellular necrosis process model for estimating conifer crown scorch - Kate J. Fuller; Leda N. Kobziar; Rodman R. Linn; Sharon M. Hood (Ecological Modelling, 2025)

Disturbance history has limited influence on subalpine fir decline - Niko J. Tutland; Olivia Santiago; Thomas R. Heydman; Kyle C. Rodman; Sarah J. Hart (Forest Ecology and Management, 2025)

Modeling the impact of smoke from prescribed fire on road visibility - Sara Brambilla; Diego Rojas; David J. Robinson; Alexander J. Josephson; Matthew A. Nelson; Rodman R. Linn (Environmental Modelling & Software, 2025)

Characterizing turbulence at a forest edge: A vorticity budget analysis around a canopy - Dorianis M. Perez; Jesse M. Canfield; Rodman R. Linn; Kevin Speer (Agricultural and Forest Meteorology, 2025)

Extreme Fire Spread Events Burn More Severely and Homogenize Postfire Landscapes in the Southwestern United States - Jessika R. McFarland; Jonathan D. Coop; Jared A. Balik; Kyle C. Rodman; Sean A. Parks; Camille S. Stevens‐Rumann (Global Change Biology, 2025)
Extreme fire spread events rapidly burn large areas with disproportionate impacts on people and ecosystems. Such events are associated with warmer and drier fire seasons and are expected to increase in the future. Our understanding of the landscape outcomes of extreme events is limited, particularly regarding whether they burn more severely or produce spatial patterns less conducive to ecosystem recovery. To assess relationships between fire spread rates and landscape burn severity patterns, we used satellite fire detections to create day‐of‐burning maps for 623 fires comprising 4267 single‐day events within forested ecoregions of the southwestern United States. We related satellite‐measured burn severity and a suite of high‐severity patch metrics to daily area burned. Extreme fire spread events (defined here as burning > 4900 ha/day) exhibited higher mean burn severity, a greater proportion of area burned severely, and increased like adjacencies between high‐severity pixels. Furthermore, increasing daily area burned also resulted in greater distances within high‐severity patches to live tree seed sources. High‐severity patch size and total high‐severity core area were substantially higher for fires containing one or more extreme spread events than for fires without an extreme event. Larger and more homogenous high‐severity patches produced during extreme events can limit tree regeneration and set the stage for protracted forest conversion. These landscape outcomes are expected to be magnified under future climate scenarios, accelerating fire‐driven forest loss and long‐term ecological change.

Wildland fire mid-story: A generative modeling approach for representative fuels - Grant Hutchings; James Gattiker; Braden Scherting; Rodman R. Linn (Environmental Modelling & Software, 2024)

The effect of terrain-influenced winds on fire spread in QUIC-Fire - David Robinson; Sara Brambilla; Julia Oliveto; Michael J. Brown; Adam Atchley; Rodman R. Linn (Environmental Modelling & Software, 2023)

DUET - Distribution of Understory using Elliptical Transport: A mechanistic model of leaf litter and herbaceous spatial distribution based on tree canopy structure - Jenna S. McDanold; Rodman R. Linn; Alex K. Jonko; Adam L. Atchley; Scott L. Goodrick; J. Kevin Hiers; Chad M. Hoffman; E. Louise Loudermilk; Joseph J. O'Brien; Russell A. Parsons; Carolyn H. Sieg; Julia A. Oliveto (Ecological Modelling, 2023)

Learning From the Study Fleet: Maintenance of a Large-Scale Reference Fleet for Northeast U.S. Fisheries - Andrew W. Jones; Katie A. Burchard; Anna M. Mercer; John J. Hoey; Michael D. Morin; Giovanni L. Gianesin; Jacob A. Wilson; Calvin R. Alexander; Brooke A. Lowman; Debra G. Duarte; David Goethel; James Ford; et al. (Frontiers in Marine Science, 2022)
Logbook data from commercial fisheries are a vital component in the machinery of management, including tracking the volume of catches and allocating catch spatially. At the same time, logbooks can provide a unique window into the ecological and sociological conditions in marine fisheries, where fishermen interact with marine species and environments frequently and broadly. Traditional logbooks, however, often are not sufficiently standardized (when personal logs), or lack the detail (when regulatory documents) required to adequately understand fisheries ecosystems. The Study Fleet program, operated by the Northeast Fisheries Science Center’s Cooperative Research Branch, was developed to address these shortfalls by engaging members of the fishing industry in collecting high-resolution catch, effort, and environmental data using electronic logbooks. Since its inception, the Study Fleet has expanded from a small project focused on collecting detailed catch information from the New England multispecies groundfish fishery to a program with a wider scope encompassing a variety of fisheries, gears, and environmental parameters from North Carolina to Maine U.S. Over the years, a number of lessons have been learned about recruiting and supporting industry partners, managing the data, evolving technical specifications, and the challenges associated with analyzing and applying self-reported fisheries data. Here we describe the current state of the program and provide summaries of the Study Fleet program operations and outcomes from 2007-2020, with an eye towards successes, challenges, and applicability of the approach in other regions. We suggest other reference fleet programs, as well as other developing fishery dependent data collections (e.g., electronic monitoring programs), develop detailed roadmaps for each data collection to keep participants engaged as collaborators, target specific fisheries to keep resources from being stretched too thin, and partner with data users early. Additionally, we suggest programs invest in the long-term participation of individual fishermen, carefully weigh the pros and cons of involvement in regulatory reporting, and plan data products and applications well in advance to ensure that the sampling scheme and granularity of the data meet the needs of stock assessment, ecosystem, and oceanographic scientists.

A changing climate is snuffing out post‐fire recovery in montane forests - Kyle C. Rodman; Thomas T. Veblen; Mike A. Battaglia; Marin E. Chambers; Paula J. Fornwalt; Zachary A. Holden; Thomas E. Kolb; Jessica R. Ouzts; Monica T. Rother (Global Ecology and Biogeography, 2020)
Aim Climate warming is increasing fire activity in many of Earth’s forested ecosystems. Because fire is a catalyst for change, investigation of post‐fire vegetation response is critical to understanding the potential for future conversions from forest to non‐forest vegetation types. We characterized the influences of climate and terrain on post‐fire tree regeneration and assessed how these biophysical factors might shape future vulnerability to wildfire‐driven forest conversion. Location Montane forests, Rocky Mountains, USA. Time period 1981–2099. Taxa studied Pinus ponderosa ; Pseudotsuga menziesii . Methods We developed a database of dendrochronological samples ( n = 717) and plots ( n = 1,301) in post‐fire environments spanning a range of topoclimatic settings. We then used statistical models to predict annual post‐fire seedling establishment suitability and total post‐fire seedling abundance from a suite of biophysical correlates. Finally, we reconstructed recent trends in post‐fire recovery and projected future dynamics using three general circulation models (GCMs) under moderate and extreme CO 2 emission scenarios. Results Though growing season (April–September) precipitation during the recent period (1981–2015) was positively associated with suitability for post‐fire tree seedling establishment, future (2021–2099) trends in precipitation were widely variable among GCMs, leading to mixed projections of future establishment suitability. In contrast, climatic water deficit (CWD), which is indicative of warm, dry conditions, was negatively associated with post‐fire seedling abundance during the recent period and was projected to increase throughout the southern Rocky Mountains in the future. Our findings suggest that future increases in CWD and an increased frequency of extreme drought years will substantially reduce post‐fire seedling densities. Main conclusions This study highlights the key roles of warming and drying in declining forest resilience to wildfire. Moisture stress, driven by macroclimate and topographic setting, will interact with wildfire activity to shape future vegetation patterns throughout the southern Rocky Mountains, USA.

The Decline of the Clearcut: 26 Years of Change in Silvicultural Practices and Implications in Minnesota - M A Windmuller-Campione; M B Russell; E Sagor; A W D’Amato; A R Ek; K J Puettmann; M G Rodman (Journal of Forestry, 2020)
Silvicultural decisions and forest-management practices in Minnesota represent the collaboration and partnership between forest managers from multiple organizations and forest researchers. To better understand current practices, trends, needs, and opportunities, Minnesota has invested in the collection of quantitative data on the application of silvicultural systems and forest-management activities in 1991, 1996, 2008, and 2017. Drawing on those data, the goal of our study is to summarize 26 years of data to characterize and quantify trends in forest-management practices. During this period of time, timberland ownership (acres) has increased, whereas harvested volume has decreased (cords). Across state, federal, county, forest industry, and tribal forest lands, which collectively represent the majority of timberlands in Minnesota, the clearcut system decreased from 91% of the harvested area in 1991 to 72 percent in 2017. In contrast, the proportion of total harvested area as part of shelterwood, seed tree, selection, and thinning treatments all more than doubled from 1991 to 2017. Factors influencing the changes relate to forest health and diseases, shifts in ownership structure, and shifts in organizational policy and/or goals. The factors identified mirror many of the trends forest managers are experiencing in other regions, nationally and internationally.

Comparing two periphyton collection methods commonly used for stream bioassessment and the development of numeric nutrient standards - Ashley R. Rodman; J. Thad Scott (Environmental Monitoring and Assessment, 2017)

Decision making in avoidance–reward conflict: a paradigm for non-human primates and humans - Demetrio Sierra-Mercado; Thilo Deckersbach; Amanda R. Arulpragasam; Tina Chou; Alexandra M. Rodman; Amanda Duffy; Eric J. McDonald; Christine A. Eckhardt; Andrew K. Corse; Navneet Kaur; Emad N. Eskandar; Darin D. Dougherty (Brain Structure and Function, 2015)

Influence of Limnological Conditions on Clostridium Botulinum Type E Presence in Eastern Lake Erie Sediments (Great Lakes, USA) - Alicia Pérez-Fuentetaja; Mark D. Clapsadl; Donald Einhouse; Paul R. Bowser; Rodman G. Getchell; W. Theodore Lee (Hydrobiologia, 2006)

Kuskonook Creek, an example of a debris flow analysis - D. F. VanDine; R. F. Rodman; P. Jordan; J. Dupas (Landslides, 2005)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)